2022
DOI: 10.18599/grs.2022.4.2
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentation model of the middle Devonian clastic succession of the South Tatar Arch, Pashyian Regional stage, Volga-Ural Oil and Gas Province, Russia

Abstract: The Pashyian Regional stage (horizon) is the main productive unit of the middle Devonian clastic succession of the South Tatar arch. This article presents, for the first time, maps of the lower and upper parts of the Pashyian, including data on sand-shale ratio, number of sand layers (reservoirs) and thickness, based on the analysis of logging data from 25,000 wells. The maps were created by spatial interpolation of Natural Neighbor and ArcGIS Pro software. The model of sedimentation of the Pashyian Regional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…At the end of the Givetian (Pashyian Regional Stage), carbonate sedimentation in the studied area completely terminated. Steady accumulation of carbonate sediments was recovered and stabilised in the studied area in the early Frasnian and continued until the global regression in the Early Visean (Silantiev et al, 2023). Transgression in the Early Frasnian for the first time extended carbonate sedimentation to shallow water environments located on tectonic arches.…”
Section: Main Sedimentation Types and Their Distribution Patternsmentioning
confidence: 82%
See 4 more Smart Citations
“…At the end of the Givetian (Pashyian Regional Stage), carbonate sedimentation in the studied area completely terminated. Steady accumulation of carbonate sediments was recovered and stabilised in the studied area in the early Frasnian and continued until the global regression in the Early Visean (Silantiev et al, 2023). Transgression in the Early Frasnian for the first time extended carbonate sedimentation to shallow water environments located on tectonic arches.…”
Section: Main Sedimentation Types and Their Distribution Patternsmentioning
confidence: 82%
“…In the works of many researchers, the origin of clastic sediments was associated with continental alluvial processes (Danilova, 2008;Loscheva et al, 2017). Meanwhile, recent studies (Silantiev et al, 2022, Miftakhutdinova, 2023 have confirmed the marine origin of these sediments and linked them to transgressive episodes of the Devonian marine basin.…”
Section: Rate and Duration Of Sediment Accumulationmentioning
confidence: 88%
See 3 more Smart Citations